Influence of Endogenous Cardiac Glycosides, Digoxin, and Marinobufagenin in the Physiology of Epithelial Cells - Alejandro Ogazon del Toro; Lidia Jimenez; Lorena Hinojosa; Jacqueline Martínez-Rendón; Aida Castillo; Marcelino Cereijido; Arturo Ponce (Cardiology Research and Practice)
Cardiac glycosides are a group of compounds widely known for their action in cardiac tissue, some of which have been found to be endogenously produced (ECG). We have previously studied the effect of ouabain, an endogenous cardiac glycoside, on the physiology of epithelial cells, and we have shown that in concentrations in the nanomolar range, it affects key properties of epithelial cells, such as tight junction, apical basolateral polarization, gap junctional intercellular communication (GJIC), and adherent junctions. In this work, we study the influence of digoxin and marinobufagenin, two other endogenously expressed cardiac glycosides, on GJIC as well as the degree of transepithelial tightness due to tight junction integrity (TJ). We evaluated GJIC by dye transfer assays and tight junction integrity by transepithelial electrical resistance (TER) measurements, as well as immunohistochemistry and western blot assays of expression of claudins 2 and 4. We found that both digoxin and marinobufagenin improve GJIC and significantly enhance the tightness of the tight junctions, as evaluated from TER measurements. Immunofluorescence assays show that both compounds promote enhanced basolateral localization of claudin-4 but not claudin 2, while densitometric analysis of western blot assays indicate a significantly increased expression of claudin 4. These changes, induced by digoxin and marinobufagenin on GJIC and TER, were not observed on MDCK-R, a modified MDCK cell line that has a genetically induced insensitive α1 subunit, indicating that Na-K-ATPase acts as a receptor mediating the actions of both ECG. Plus, the fact that the effect of both cardiac glycosides was suppressed by incubation with PP2, an inhibitor of c-Src kinase, PD98059, an inhibitor of mitogen extracellular kinase-1 and Y-27632, a selective inhibitor of ROCK, and a Rho-associated protein kinase, indicate altogether that the signaling pathways involved include c-Src and ERK1/2, as well as Rho-ROCK. These results widen and strengthen our general hypothesis that a very important physiological role of ECG is the control of the epithelial phenotype and the regulation of cell-cell contacts.